The Quality-Profit Assumption - Kinser, Kevin (International Higher Education, 2013)
The profit motive is typically linked to lower quality in higher education. But there are several routes to profitability that do not presume a decline in quality, but rather take advantage of price and service strategies that generate revenue without significant impact on the academic program. Quality, therefore, is not determined by the profit status of the institution.